Implementasi Media Augmented Reality dalam Pembelajaran Bangun Ruang di Sekolah Dasar (SD) Ta’allumul Huda Bumiayu - Eka Farida Fasha; Rimbatmojo, Sigit; Ghulam Arif Rizal; Khurotul Aeni; Asep Saeful Millah (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Students' understanding of three-dimensional geometric concepts at SD Ta’allumul Huda Bumiayu remains relatively low, primarily due to the limited availability of visual learning media. The purpose of this training activity is to introduce the use of Augmented Reality (AR) applications as an interactive learning tool. The program was implemented in three stages: preparation, implementation, and evaluation. In the preparation stage, a site survey and development of learning materials were conducted. During the implementation stage, the team presented geometry lessons using AR media to fifth-grade students. The evaluation stage involved data collection and analysis, conducted through observation, semi-structured interviews, and student perception questionnaires. The results indicated an increase in student engagement and understanding of spatial concepts. A total of 93% of students stated that the material was more engaging, while 87% reported improved comprehension of the elements and properties of geometric shapes. Teachers also found the AR media to be practical and aligned with learning objectives. These findings suggest that the use of AR technology serves as an innovative solution to enhance contextual learning quality in primary school mathematics education.